Galia Golan : an academic pioneer on the Soviet Union, peace and conflict studies, and a peace and feminist activist /: an academic pioneer on the Soviet Union, peace and conflict studies, and a peace and feminist activist. ([2019]) - Golan, Galia
No abstract available